Pengaruh Kepemimpinan Camat Terhadap Kesadaran Masyarakat Dalam Membayar Pajak Bumi dan Bangunan Di Kecamatan Eris Kabupaten Minahasa - Sumarauw, Stefi Maria; Rares, Joyce Jacinta; Kiyai, Burhanuddin (Sam Ratulangi University, 2015)
ABSTRACT : The Earth and building tax is a direct tax that is withheld by the Central Government, butthe results received are intended for community interests in the area corresponding to the layout and thetax object. The existence of tendencies and a sense of reluctance from some community Districts that paytaxes in Eris views from various things relating to public awareness itself due to a weak economy thatfactor in the work of inner as farmers, the Bill that is not in accordance with the objects of taxation andthere are people who deliberately don't want to pay UN.. Therefore, this research aims to know theinfluence of the leadership of the Head of community awareness in the Earth and buildings to pay taxes.The independent variables (free) in this study was leadership of (X) is a capacity that has theability to affect or right to steer, or encourage a person to do everything which is the wisdom or acommand for a particular purpose. The dependent variable (tied) in the penenlitian this is the awarenessof UN Pay as a Variable (Y) the existence of public awareness will encourage a strong desire to improveand develop common interests in order to achieve a better life. The type of research used in this study is aresearch method of quantitative analysis with descriptive statistics, with a view to seeking influencesbetween the dependent variable and independent variable.Overall analysis of the results indicates that the leadership of the Head has a positive influence on theAwareness of society in the pay of the UN in the Sub-District of Eris. As the results of this research as wellas the theoretical opinion then it can be stated that the leadership of the Head has a positive influence onthe Awareness of society in the pay of the UN.Keywords: Head Of Leadership, Community Awareness In Pay The Earth and building tax